Application of the System Development Life Cycle Method for the South Jakarta Area Search System with User Acceptance Test - Rima Tamara Aldisa (IJISTECH (International Journal of Information System and Technology), 2022)
A system designed to assist prospective new students in providing, knowing the final results of the lectures or campuses that are expected to be in the south Jakarta area. This system is built on an android based which can be installed by users easily, quickly. Users here are prospective new students primarily, this system helps in providing information, provides a map of campus routes, campuses or majors on campus and makes it easier for new students to determine where to study. From the research conducted, it provides 7 questions that produce an android-based system using the System Development Life method. The results of the test using the UAT User Acceptance Test with 30 prospective new student participants who want to continue their studies to the undergraduate level which we apply to install this application on each participant's smartphone. User Acceptance Test testing of 89.14%, meaning that results indicate that the Application of the System Development Life Cycle Method for the South Jakarta Regional Study Place Search System with User Acceptance Test was built can be used by prospective new students